Hepatotoxic Test Of Burdock Roots (Arctium Lappa L) On Histopathology Hepar Of Male White Rats (Rattus Norvegicus - Wigati, Atika Nur; Faizal, Imam Agus; Puspodewi, Dini (Poltekkes Kemenkes Semarang, 2024)
Burdock (Arctium lappa L) is a homologous medical plant that is considered having with many advantages as a traditional medicine. Burdock root contains several substances such as inulin, essential oils, tannins, quercetin,iron, and arctigenin. This study was conducted to determine investigates effect of burdock root extract on the hepar histopathology of male white rats. This study used an experimental method with 20 rats and was divided into 4 groups. The positive control group was given gentamicin induction intramuscularly. The negative control group was given distilled water. The 150 mg/kgBW dose group and the 450 mg/kgBW dose group were given burdock root extract with treatment for 14 days and surgery was performed oin the 15th day to take hepatic organs to make histopathology preparations. The results of the this study were are interpreted by scoring and tabulated, the analysis was is done carried out descriptively with the results, in positive control group found mild damage, the negative group found no damage, in the extract dose group 150mg/kgBW found necrosis, bleeding and vacuolization, and in the extract dose group 450mg/kgBW found degeneration, necrosis, bleeding and vacuolization. The conclusion of this study is the hepatoprotective potential of burdock root extract (Arctium lappa L.) and its related effects on liver tissue in an experimental model. On the other hand, parasitic worms Taenia taeniaeformis were found in the liver which interfered with the interpretation of the results.